2021
DOI: 10.3390/healthcare9010099
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Scope, Inclusivity, and Integration of Music in Healthcare: Recent Developments, Research Illustration, and Future Direction

Abstract: This paper is in three sections. Section One presents a historical overview of international initiatives that have expanded the role of music in healthcare, from the initial formalization of music therapy to its more research-based rehabilitation focus to recent decades that have seen an increasing role for professional and community musicians, paraprofessional music services, music-oriented service organizations, and a very large increase in medical funding for music effects. “Music Care” is a particular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Outcome data were collected pre- and post- implementation of the music care initiative to understand the impact of music care on residents’ lived experience of isolation and loneliness. These quantitative results are reported elsewhere [ 27 ].…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Outcome data were collected pre- and post- implementation of the music care initiative to understand the impact of music care on residents’ lived experience of isolation and loneliness. These quantitative results are reported elsewhere [ 27 ].…”
Section: Methodssupporting
confidence: 81%
“…Despite staffing challenges and shortages in LTC homes in Ontario, the implementation of the MCP program significantly decreased self-perceived isolation scores of participating residents [ 27 ]. In addition to understanding the resident outcomes associated with MCP, it is critical to gain an understanding of the lived experience of staff, volunteers, and residents who were part of the MCP initiative, especially given the systemic challenges (such as staff shortages, caregiver burnout, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by another study that found that by the end of a social prescription of community exercise classes, loneliness scores decreased and participant's scores on social connectedness improved (Mays, Kim, Rosales, Au, & Rosen, 2020). Some care homes that introduced music activities such as choirs reported a decrease in loneliness/isolation, although this effect was inconsistent (Foster, Pearson, Berends, & Mackinnon, 2021). Qualitative reports from further studies support a decrease in loneliness from social group interventions (Coll‐Planas et al, 2021).…”
Section: Social Connectionmentioning
confidence: 99%
“…This was supported by another visual arts program that involved viewing and then making art, which found a decrease in negative affect over a 12‐week intervention (Windle et al, 2018). A music intervention in long‐term care homes found a decrease in depression and aggression for some homes following the intervention (Foster et al, 2021). These results suggest that social prescribing may be beneficial for older adults' mental health.…”
Section: Improvement In Mental Health and Wellbeingmentioning
confidence: 99%
“…Music Connects Us involves a range of professional, semi-professional and student musicians who create musical experiences, and is part of a broader movement to increase use of music in care environments. This broader movement involves a range of initiatives including: music therapy, where trained therapists use music prescriptively for health and wellbeing; music medicine, where the sonic, vibrational, and rhythmic properties of music and sound are used as medicine; other kinds of music-based programming, like offering care home residents personalized playlists; and organizations like the Room 217 foundation which offers caregivers, with and without musical skill, the training and resources to integrate music into many aspects of their practice in order to deliver ‘music care’ [ 56 ]. Music Connects Us primarily addresses the music care domain of musicking, which is the promotion of spontaneous and informal engagement with music (e.g., listening, music-making) [ 57 ], and offers residents a specialized, time-limited musical experience.…”
Section: Discussionmentioning
confidence: 99%